Impact of computerised accounting system in ensuring effective financial control in local government authorities in Tanzania: Case study Musoma District Council - Munisi, Nsia Y. (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for award of the degree of Master of Science in Accounting and Finance of Mzumbe University